Motor Development in Early Childhood: Inhibiting Factors - Literature Review - Fauziah, Ella; Sumaryanti, Sumaryanti; Suhartini, Bernadeta; Budayati, Eka Swasta; Putra, Martinez Edison; Suryadi, Didi (Universitas Tanjungpura, 2024)
Child development needs to be monitored as early as possible, as it can contribute to subsequent development. This article conducts a thorough literature review to explain the inhibiting factors that impact on child development, especially motor development in early childhood. Where motor development at an early age is a major milestone for subsequent motor development. This study aims to review scientific literature on inhibiting factors in motor development for early childhood. The database search used ScienceDirect to select articles containing information on motor development in early childhood. The search was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. After the exclusion criteria were met, 13 articles were categorized. In the first group, there were factors that inhibit development in children, such as premature birth, congenital heart disease, and sleeping habits can inhibit motor development in early childhood. The results in the second group informed that the lack of nutritional intake and breastfeeding, as well as the provision of sugary foods can have a negative impact on child development, especially gross motor development. The results of the third group explained that environmental factors, forms of play, and parental knowledge can affect motor development in children, especially fundamental motor skills. Therefore, it is important to have a basic knowledge of the factors that can hinder children's development and the supporting factors that can improve children's development according to their age.